2018
DOI: 10.1111/andr.12543
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive insight into functional interaction between GNB3 C825T and eNOS T‐786C, G894T gene polymorphisms and association with susceptibility to diabetic erectile dysfunction

Abstract: Our study gave a comprehensive insight into functional interaction between GNB3 and eNOS gene polymorphisms and suggests that the eNOS G894T and T-786C variants are strong predisposing factors of VED susceptibility within men with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…In addition to diabetes, there have been numerous human and animal studies that have shown the abnormal effects of lipid-related tests on ED, especially when associated with diabetes. Generally, dyslipidemia is a risk factor for ED patients who also suffer from diabetes (15).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to diabetes, there have been numerous human and animal studies that have shown the abnormal effects of lipid-related tests on ED, especially when associated with diabetes. Generally, dyslipidemia is a risk factor for ED patients who also suffer from diabetes (15).…”
Section: Introductionmentioning
confidence: 99%
“…One of the eNOS gene variants is G894T [49] . The singlenucleotide polymorphism at position 298 in exon 7 led to the transversion of guanine with thymine, resulting in the substitution of glutamate with aspartate in the mature protein [49][50][51][52] . This polymorphism increases the selective proteolytic cleavage of endothelial cells and vascular tissue leading to the reduction in the NOS activity and subsequent decrease in the production of vascular NO.…”
Section: Genetic Factors Associated With Sexual Dysfunction In T2dmmentioning
confidence: 99%